Modified Ti3C2TX composite photocatalyst as well as preparation method and application thereof

By constructing the Schottky heterojunction structure of Ti3C2TX and Bi2MoO6, the existing photocatalysts have been solved, and the effective antibiotic degradation effect is achieved, and the catalytic function is significantly improved.

CN119869574AInactive Publication Date: 2025-04-25NANJING NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510023336.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing Ti3C2TX photocatalysts have problems such as low solar energy conversion efficiency, poor carrier separation effect and insufficient interfacial reaction activity, which makes it difficult to meet the practical application standards.

Method used

By constructing the Schottky heterojunction structure of Ti3C2TX and Bi2MoO6, a 2D/2D sheet patch layer-like shape is formed, which enhances light absorption, interface area and local photothermal effect, and jointly improves the utilization rate and catalytic function of light.

Benefits of technology

Effectively inhibit the recombination of photogenerated electrons-holes, improve the utilization rate of light, enhance the catalytic activity of light, significantly improve the degradation efficiency and degree of antibiotics, and the catalytic function of the catalyst is increased by 2.53 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869574A_ABST
    Figure CN119869574A_ABST
Patent Text Reader

Abstract

The invention discloses a modified Ti3C2TX composite photocatalyst and a preparation method and application thereof.The catalyst comprises a carrier Ti3C2TX nanosheet and a Bi2MoO6 nanosheet growing on the carrier, the Ti3C2TX nanosheet and the Bi2MoO6 nanosheet form a Schottky heterojunction structure, and the catalyst is of a 2D / 2D patch layered morphological structure; the preparation method comprises the following steps: dispersing single-layer Ti3C2TX in water containing bismuth salt, adding molybdenum salt and ammonium salt, uniformly mixing, and carrying out hydrothermal reaction to obtain the catalyst. Ti3C2TX and Bi2MoO6 are combined to form a 2D / 2D patch layered morphological structure, so that photo-induced electron-hole recombination can be effectively inhibited, transfer of photo-induced charges is promoted, a synergistic effect is formed with an LPE effect, the molecular weight and diversity of molecules are reduced in the photocatalytic degradation process, and efficient photocatalytic degradation of organic pollutants is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photocatalyst, in particular to a modified Ti3C2T X Composite photocatalyst and its preparation method and application. Background Art

[0002] In recent years, the abuse of antibiotics has exacerbated environmental pollution and ecological damage. Photocatalytic technology is based on semiconductors and their derivative materials as a medium, with solar energy as a power source. With its advantages of being pollution-free, economical and efficient, it has become the most promising way to efficiently remove antibiotics from water. X Due to its full spectrum absorption, high photothermal conversion rate, easy modification and high carrier mobility, it has become the focus of recent research on photocatalytic degradation of antibiotics in water. However, it is limited by low solar energy conversion efficiency, poor carrier separation and insufficient interfacial reaction activity, and it is difficult for this technology to meet the standards for practical application. Summary of the invention

[0003] Purpose of the invention: The first purpose of the present invention is to provide a modified Ti3C2T3 with high photocatalytic full spectrum absorption and degradation efficiency. X Composite photocatalyst; The second object of the present invention is to provide the modified Ti3C2T X Preparation method of composite photocatalyst; The third object of the present invention is to provide the modified Ti3C2T X Application of composite photocatalyst degradation in the degradation of antibiotics.

[0004] Technical solution: The modified Ti3C2T X Composite photocatalyst including carrier Ti3C2T X Nanosheets and grown on Ti3C2T X Bi2MoO6 nanosheets, Ti3C2T X The nanosheets and the Bi2MoO6 nanosheets form a Schottky heterojunction structure, and the catalyst is a 2D / 2D sheet-to-sheet layered morphology structure.

[0005] Ti3C2T X Nanosheets and Bi2MoO6 nanosheets construct Schottky heterojunctions while maintaining Ti3C2T X Based on the redox performance of Ti3C2T, it effectively inhibits the recombination of photogenerated electrons and holes and improves the utilization rate of light. More importantly, Ti3C2T XThe 2D / 2D sheet-to-sheet layered morphology between the nanosheets and the Bi2MoO6 nanosheets enhances light absorption, increases the interface area, and reduces the transfer distance, forming a local photothermal effect (LPE). LPE can drive photons to generate heat energy, promote charge carrier transfer and separation of electron-hole pairs, and the generated heat energy will effectively improve the degradation efficiency and degree of organic pollutants. LPE and Schottky heterojunction work together to further improve the catalytic function of the catalyst.

[0006] Preferably, the Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 1~8∶122.

[0007] Further preferably, the Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 1-4:122.

[0008] The mass of Bi2MoO6 nanosheets was calculated based on the mass of the added bismuth salt and molybdenum salt, and the mass of Ti3C2T X The mass ratio of Ti3C2T nanosheets to Bi2MoO6 nanosheets. X When the mass ratio of nanosheets to Bi2MoO6 nanosheets is 2:122, the produced catalyst has the highest catalytic efficiency for organic pollutants. A ratio higher or lower than this ratio will result in a decrease in catalytic efficiency.

[0009] The modified Ti3C2T X The preparation method of the composite photocatalyst comprises the following steps:

[0010] (1) Dissolve lithium fluoride in concentrated hydrochloric acid, stir, add Ti3AlC2 powder, remove aluminum through etching reaction, and obtain multilayer Ti3C2T X ; Multilayer Ti3C2T X The solid was dispersed in water, ultrasonicated in an ice bath, and the supernatant was collected by centrifugation and freeze-dried to obtain a single layer of Ti3C2T X ;

[0011] (2) The single-layer Ti3C2T prepared in (1) X Disperse in water containing bismuth salt, then add molybdenum salt and ammonium salt, mix evenly, and perform hydrothermal reaction to form Ti3C2T X The Ti3C2T X Modified composite photocatalyst.

[0012] Preferably, in step (1), the temperature of the etching reaction is 30-35° C., and the reaction time is 24-32 hours.

[0013] Preferably, in step (2), the temperature of the hydrothermal reaction is 100 to 180°C and the reaction time is 10 to 15 hours.

[0014] Preferably, in step (2), the mass ratio of the Ti element, the Bi element, and the Mo element is (0.01-0.08) : (1.80-1.95) : (0.40-0.50).

[0015] Preferably, in step (2), the ammonium salt is hexadecyltrimethylammonium bromide (CTAB). The ammonium salt has the function of promoting dispersion in the material preparation process, so that the obtained material presents a dispersed lamellar structure. Preferably, the Ti3C2T X The mass volume ratio of bismuth salt, molybdenum salt, ammonium salt and water is (10-80) mg: (1800-2200) mg: (450-520) mg: 100 mg: 70 mL.

[0016] Preferably, in step (2), the bismuth salt is bismuth nitrate pentahydrate, and the molybdenum salt is sodium molybdate dihydrate.

[0017] The modified Ti3C2T X Application of composite photocatalysts in degradation of antibiotics.

[0018] Invention mechanism: MXene (Ti3C2T X ) has excellent light-to-heat conversion performance and has been used in photocatalytic degradation of pollutants. X The appropriate structure can be used to construct a Schottky heterostructure with Bi2MoO6. X Based on the redox properties of Ti3C2T, the photogenerated electron-hole recombination is effectively inhibited and the utilization rate of light is improved, which improves the degradation effect of antibiotics in water. It is a simple and effective control strategy to enhance the photocatalytic activity of materials. Under the graded solar energy utilization (GSU) strategy, Bi2MoO6 can effectively absorb short-wavelength sunlight to generate photogenerated carriers, and Ti3C2T X Convert long-wave sunlight into thermal energy, thereby maximizing the use of solar energy and achieving a wide range of applications under full-spectrum irradiation.

[0019] n-type semiconductor (Bi2MoO6) and metal-like materials (Ti3C2T X ) bonding to form a 2D / 2D morphology structure, due to enhanced light absorption, large interface area and reduced transfer distance, thus having a local photothermal effect (LPE). LPE can drive photons to generate heat energy, promote charge carrier transfer and separation of electron-hole pairs, and the generated heat energy will effectively improve the degradation efficiency and degree of organic pollutants.

[0020] There is a synergistic effect between the local photothermal effect (LPE) and the heterostructure. On the one hand, LPE can drive photons to generate heat energy, promote charge carrier transfer and separation of electron-hole pairs, and the generated heat energy will effectively improve the degradation efficiency and degree of organic pollutants; on the other hand, n-type semiconductors (Bi2MoO6) and metal-like materials (Ti3C2T X ) bonding to form a 2D / 2D morphology structure, which lays a solid foundation for LPE due to the enhanced light absorption, large interfacial area and reduced transfer distance.

[0021] Modified Ti3C2T prepared by the present invention X Schematic diagram of the photocatalytic reaction mechanism of the composite photocatalyst Figure 1 shown.

[0022] Ti3C2T X A Schottky heterojunction is formed between Ti3C2T and Bi2MoO6, and the uniformly dispersed sheet-to-sheet (2D / 2D) heterojunction is conducive to the effective migration of carriers. In the photocatalytic degradation of pollutants, due to the built-in electric field at the Schottky heterojunction interface, Ti3C2T X The photoexcited electrons in the conduction band spontaneously transfer to the valence band of Bi2MoO6, consuming the remaining holes in Bi2MoO6, thereby effectively achieving efficient spatial separation of photogenerated electrons and holes and maintaining the strongest redox ability of the system to improve the performance of the system in photocatalytic degradation of pollutants. On the other hand, the difference in energy band positions is used to inhibit the rapid recombination of electron-hole pairs, thereby improving the utilization rate of light and the ability to degrade pollutants.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) By X Modified Ti3C2T with Bi2MoO6 X The composite photocatalyst forms a 2D / 2D sheet-patch layered morphology structure, which can effectively inhibit the recombination of photogenerated electrons and holes, promote the transfer of photogenerated charges, and form a synergistic effect with the LPE effect, thereby reducing the molecular weight and diversity of molecules during the photocatalytic degradation process, and efficiently realizing the photocatalytic degradation of organic pollutants; (2) The preparation method is simple, the raw materials are cheap and easy to obtain, the method is green and simple, and it has the premise of being able to be put into large-scale production in the future, and has good application prospects in solving problems such as future energy shortages; (3) The modified Ti3C2T X The composite photocatalyst was used to catalyze the degradation of organic pollutants. The photocatalytic activity of the 2D / 2D Schottky heterojunction increased by 2.53 times, which was significantly better than that of the original Ti3C2T X (1.11 times), original Bi2MoO X(1.23 times), and 2D@2D morphology (1.80 times), which have broad prospects in the practical application of photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The modified Ti3C2T prepared by the present invention X Schematic diagram of the photocatalytic reaction mechanism of the composite photocatalyst;

[0025] Figure 2 The modified Ti3C2T prepared in Example 2 X SEM image of the composite photocatalyst;

[0026] Figure 3 The modified Ti3C2T prepared in Example 2 X Transmission electron microscopy image of the composite photocatalyst;

[0027] Figure 4 The modified Ti3C2T prepared in Example 2 X X-ray diffraction pattern of the composite photocatalyst;

[0028] Figure 5 The modified Ti3C2T prepared in Comparative Example 3 X Field emission scanning electron microscopy image of the composite photocatalyst BM@MN-20;

[0029] Figure 6 The modified Ti3C2T prepared in Examples 1 to 3 X Photocatalytic degradation efficiency diagram of NOR of the composite photocatalyst and the materials prepared in Comparative Examples 1 to 3;

[0030] Figure 7 , Figure 8 and Fig. 9 The modified Ti3C2T prepared in Example 2 and Comparative Example 3 are X Superoxide radicals (·O2 - ), hydroxyl radical (·OH), electron paramagnetic resonance hole (h + )’s EPR spectrum;

[0031] Fig.10 The modified Ti3C2T prepared in Example 2, Comparative Example 2 and Comparative Example 3 X Kapp diagram of photocatalytic degradation of NOR by composite photocatalyst;

[0032] Fig.11 The modified Ti3C2T prepared in Example 2 X Cyclic stability test diagram of composite photocatalyst. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below in conjunction with embodiments.

[0034] Example 1

[0035] Modified Ti3C2T X The composite photocatalyst, the preparation method thereof comprises the following steps:

[0036] (1) 2 g of LiF was dissolved in 20 mL of 9 M concentrated hydrochloric acid solution, stirred evenly, and then 2 g of Ti3AlC2 powder was added. After strong heat release in the etching reaction, the reaction was cooled to room temperature and then reacted in an oil bath at 30°C for 24 hours. After the reaction was completed, the black suspension was washed with deionized water until the solution pH was ≈ 7. The black precipitate was collected and dried at 60°C in vacuum overnight. The obtained product was redispersed in deionized water, ultrasonically treated in an ice bath for 30 min, and the obtained solution was centrifuged to obtain a supernatant, which was freeze-dried to obtain a single layer of Ti3C2T X Nanosheets;

[0037] (2) Take 10 mg of the prepared single-layer Ti3C2T X The nanosheets (containing 7.19 mg of titanium element) were ultrasonically dispersed in 25 mL of deionized water containing 1850 mg of bismuth nitrate pentahydrate (containing 797.10 mg of bismuth element), and then 25 mL of deionized water containing 450 mg of sodium molybdate dihydrate (containing 178.46 mg of molybdenum element) and 80 mg of hexadecyltrimethylammonium bromide were added. The mixture was stirred continuously for 30 min, and the mixture was reacted at a temperature of 120 ° C for 12 hours. After cooling, the precipitate was collected by centrifugation, washed with deionized water and ethanol, and dried overnight to obtain modified Ti3C2T X Composite photocatalyst BM / MN-10, in which Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 1:122.

[0038] Example 2

[0039] On the basis of Example 1, the single layer Ti3C2T X The mass of the nanosheets was changed to 20 mg, and the other conditions remained unchanged to obtain modified Ti3C2T X Composite photocatalyst BM / MN-20, in which Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 2:122.

[0040] Example 3

[0041] On the basis of Example 1, the single layer Ti3C2T X The mass of the nanosheets was changed to 40 mg, and the other conditions remained unchanged to obtain modified Ti3C2T XComposite photocatalyst BM / MN-40, in which Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 4:122.

[0042] Example 4

[0043] On the basis of Example 1, the single layer Ti3C2T X The mass of the nanosheets was changed to 60 mg, and the other conditions remained unchanged to obtain modified Ti3C2T X Composite photocatalyst BM / MN-60, in which Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 6:122.

[0044] Example 5

[0045] On the basis of Example 1, the single layer Ti3C2T X The mass of the nanosheets was changed to 80 mg, and the other conditions remained unchanged to obtain modified Ti3C2T X Composite photocatalyst BM / MN-80, in which Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 8:122.

[0046] Comparative Example 1

[0047] Based on Example 2, only step (1) is performed to obtain Ti3C2T X Nano, the other conditions remain unchanged.

[0048] Comparative Example 2

[0049] Based on Example 2, step (2) does not add Ti3C2T X Nanosheets, only Bi2MoO6 nanosheets were synthesized, and the other conditions remained unchanged.

[0050] Comparative Example 3

[0051] This comparative example provides a Bi2MoO6@Ti3C2T X Schottky heterojunction photocatalyst and its preparation method, the main difference between the catalyst and Example 2 is that the production method of the catalyst is epitaxial growth method, and its specific preparation method is as follows:

[0052] Step (1) is the same as in Example 2 to obtain Ti3C2T X Nanosheets.

[0053] (2) Take 20 mg of Ti3C2T prepared in step (1) XThe nanosheets were ultrasonically dispersed in 35 mL of deionized water containing 1940 mg of bismuth nitrate (containing 835.88 mg of bismuth element), and then 35 mL of sodium molybdate dihydrate containing 484 mg (containing 191.94 mg of molybdenum element) was added and stirred for 30 minutes. The mixture was kept at 160 ° C for 12 hours. After cooling, the resulting precipitate was collected by centrifugation, washed with deionized water and ethanol, and dried overnight to obtain modified Ti3C2T X Composite photocatalyst BM@MN-20.

[0054] Structural characterization

[0055] The modified Ti3C2T synthesized in Example 2 X Structural characterization of the composite photocatalyst.

[0056] Figure 2 and Figure 3 The modified Ti3C2T prepared in Example 2 are X SEM and TEM images of the composite photocatalyst. Figure 2 It can be seen that Bi2MoO6 nanosheets were observed to grow on Ti3C2T X The surface of the film forms a uniformly dispersed layered morphology; Figure 3 It can be seen that the lattice fringes of the two monomers can be clearly observed at the heterojunction interface, indicating that the two materials are successfully composited.

[0057] Figure 4 The modified Ti3C2T prepared in Example 2 X X-ray diffraction pattern of the composite photocatalyst. It can be seen from the figure that Ti3C2T X The characteristic peaks of Bi2MoO6 further illustrate the close combination of the two materials.

[0058] Figure 5 The modified Ti3C2T prepared in Comparative Example 3 X Field emission scanning electron microscopy image of the composite photocatalyst BM@MN-20. It can be seen from the image that BM@MN-20 presents the morphology of a coated layer.

[0059] Performance Characterization

[0060] 1. Modified Ti3C2T synthesized in Examples 1 to 3 X The photocatalytic performance of the composite photocatalyst and the catalysts synthesized in Comparative Examples 1 to 3 were tested.

[0061] Test method: The photocatalytic degradation performance was evaluated using a photocatalytic reactor equipped with a 300W xenon lamp. 20 mg of the prepared photocatalyst was completely dispersed in 50 mL of norfloxacin (NOR) aqueous solution (20 ppm) and ultrasonically treated. The mixture was stirred in the dark for 30 min to reach adsorption equilibrium. At a given time interval, 3 mL of the reaction solution was filtered with a 0.22 μm filter. Then, the NOR concentration of the sample was determined by high performance liquid chromatography (Agilent 1260).

[0062] Figure 6 The modified Ti3C2T prepared in Examples 1 to 3 X The photocatalytic degradation efficiency of NOR by the composite photocatalyst is shown in the figure. It can be seen that under the condition of no temperature control (no circulating water), the modified Ti3C2T prepared in Examples 1 to 3 X The degradation k values ​​of NOR of composite photocatalysts BM / MN-10, BM / MN-20, and BM / MN-40 are 0.032, 0.068, and 0.051 min, respectively. -1 , the catalyst Ti3C2T prepared in Comparative Examples 1 to 3 X The degradation k values ​​of NOR of nano- and Bi2MoO6 nanosheets BM@MN-20 are 0.001, 0.014, and 0.019 min, respectively. -1 .

[0063] From the catalytic effect data of Examples 1 to 3, it can be seen that with different mass Ti3C2T X The catalytic efficiency changes when nanosheets are added. This is because different quality Ti3C2T X The photocatalytic degradation efficiency will be reduced if too little or too much nanosheets are added.

[0064] The catalytic effect of Comparative Example 1 is lower than that of Example 2. This is because Bi2MoO6 material is not added to prepare the composite material, and the photocatalytic reaction cannot proceed.

[0065] The catalytic effect of Comparative Example 2 is lower than that of Example 2 because no Ti3C2T X The degradation efficiency of composite materials prepared from nanosheet materials is low.

[0066] The catalytic effect of Comparative Example 3 is reduced compared with that of Example 2. This is because the composite materials formed have different morphologies, and the photocatalytic photothermal efficiency of the sheet-to-sheet morphology is better than that of the wrapped morphology.

[0067] 2. Catalyst produces superoxide radicals (·O 2- ), hydroxyl radical (·OH), electron paramagnetic resonance hole (h + )test.

[0068] Figures 6 to 8The modified Ti3C2T prepared in Example 2 and Comparative Example 3 are X Superoxide radicals (·O 2- ), hydroxyl radical (·OH), electron paramagnetic resonance hole (h + )’s EPR spectrum.

[0069] As shown in Figures 7 to 9, both catalysts produced superoxide radicals (·O 2- )( Figure 7 ), hydroxyl radical (·OH) Figure 8 ) and photogenerated holes (h + )( Fig. 9 ), but the signals of these three substances in the catalyst BM / MN-20 prepared in Example 2 are stronger than those in the catalyst BM@MN-20 prepared in Comparative Example 3. This shows that BM / MN-20 exhibits better photogenerated carrier separation efficiency and photocatalytic activity under the same conditions, which strongly supports that the 2D / 2D sheet-to-sheet morphology is more conducive to achieving significant LPE enhancement.

[0070] 3. K test of photocatalytic degradation of NOR

[0071] Test method: A photocatalytic reactor equipped with a 300W xenon lamp (Nanjing Xujiang) was used to evaluate its photocatalytic degradation performance. The antibiotic NOR was selected as a model organic micropollutant with a concentration of 20ppm. Based on the adsorption equilibrium experiment, the dark adsorption time was determined to be 30 minutes. During the reaction, 3mL of the reaction sample was taken every 30 minutes, and the NOR concentration was measured by high performance liquid chromatography after the catalyst particles were removed through a 0.22μm filter membrane.

[0072] Fig.10 The modified Ti3C2T prepared in Example 2, Comparative Example 2 and Comparative Example 3 X Kapp of the composite photocatalyst for photocatalytic degradation of NOR.

[0073] Depend on Fig.10 It can be seen that in the absence of circulating water (no temperature control), the photocatalyst BM / MN-20 with the best composite ratio prepared in Example 2 showed excellent catalytic decomposition efficiency of NOR, and the apparent reaction rate constant was calculated to be 0.068 min -1 , which is 2.53 times that of BM / MN-20 in the case of circulating water (temperature control). The rate constant (kapp) of NOR degradation of BM / MN-20 prepared in Example 2 increased by 1.28 times and 1.80 times over EG-Bi2MoO6 prepared in Comparative Example 2 and BM@MN-20 prepared in Comparative Example 3, respectively. In summary, these findings strongly support that 2D / 2D sheet patch morphology is more conducive to the enhancement of catalyst performance.

[0074] 4. Catalyst stability test

[0075] Fig.11 The modified Ti3C2T prepared in Example 2 X Cyclic stability test diagram of composite photocatalyst. Fig.11 It can be seen that after three cyclic degradation experiments, BM / MN-20 still maintained high photocatalytic activity, showing excellent stability and reliability.

Claims

1. A modified Ti3C2T X A composite photocatalyst, characterized in that Including carrier Ti3C2T X Nanosheets and grown on Ti3C2T X Bi2MoO6 nanosheets, Ti3C2T X The nanosheets and the Bi2MoO6 nanosheets form a Schottky heterojunction structure, and the catalyst is a 2D / 2D sheet-to-sheet layered morphology structure.

2. The modified Ti3C2T according to claim 1 X A composite photocatalyst, characterized in that The Ti3C2T X The mass ratio of nanosheets to Bi2MoO6 nanosheets is 1~8∶122.

3. A modified Ti3C2T3 according to claim 1 or 2 X The method for preparing a composite photocatalyst is characterized in that: The following steps are involved: (1) Dissolve lithium fluoride in concentrated hydrochloric acid, stir, add Ti3AlC2 powder, remove aluminum through etching reaction, and obtain multilayer Ti3C2T X ; Multilayer Ti3C2T X The solid was dispersed in water, ultrasonicated in an ice bath, and the supernatant was collected by centrifugation and freeze-dried to obtain a single layer of Ti3C2T X ; (2) The single-layer Ti3C2T prepared in (1) X Disperse in water containing bismuth salt, add molybdenum salt and ammonium salt, mix well, and perform hydrothermal reaction to form Ti3C2T X Bi2MoO6 is generated in situ on the surface to obtain the Ti3C2T X Modified composite photocatalyst.

4. The modified Ti3C2T3 according to claim 3 X The method for preparing a composite photocatalyst is characterized in that: In step (2), the ammonium salt is hexadecyltrimethylammonium bromide.

5. The modified Ti3C2T3 according to claim 3 X The method for preparing a composite photocatalyst is characterized in that: In step (1), the temperature of the etching reaction is 30-35° C., and the reaction time is 24-32 hours.

6. The modified Ti3C2T3 according to claim 3 X The method for preparing a composite photocatalyst is characterized in that: In step (2), the temperature of the hydrothermal reaction is 100 to 180° C., and the reaction time is 10 to 15 hours.

7. The modified Ti3C2T3 according to claim 3 X The method for preparing a composite photocatalyst is characterized in that: In step (2), the Ti3C2T X The mass volume ratio of bismuth salt, molybdenum salt, ammonium salt and water is (10-80) mg: (1800-2200) mg: (450-520) mg: 100 mg: 70 mL.

8. The modified Ti3C2T3 according to claim 3 X The method for preparing a composite photocatalyst is characterized in that: In step (2), the bismuth salt is bismuth nitrate pentahydrate.

9. The modified Ti3C2T3 according to claim 3 X The method for preparing a composite photocatalyst is characterized in that: In step (2), the molybdenum salt is sodium molybdate dihydrate.

10. A modified Ti3C2T3 according to claim 1 or 2 X Application of composite photocatalysts in degradation of antibiotics.

Citation Information

Patent Citations

  • MXene-based bismuth-based photocatalytic composite membrane and preparation method thereof

    CN111822028A

  • Heterojunction photocatalyst with high catalytic activity and preparation method and application thereof

    CN112892523A